In vitro corrosion behaviour of phenolic coated nickel–titanium surfaces. Issue 1 (10th February 2020) - Longela, Simon; Chatzitakis, Athanasios
Abstract : The biocompatibility of implantable nickel–titanium biomaterials relies on the quality of their surfaces. In this study, nickel–titanium surfaces are coated with phenolic thin films of tannic acid and pyrogallol with the purpose of studying their corrosion resistance in physiological environments. Three tests are performed: the open‐circuit potential test, potentiodynamic polarisation and potentiostatic electrochemical impedance spectroscopy. Polarisation measurements are scrutinised in order to gain knowledge concerning the kinetics of the cathodic and anodic reactions, while the open‐circuit potentials and impedance spectroscopy help to study the electrolyte–surficial interactions. It is found that coating nitinol with polyphenols results in the depletion of the native oxide layer and thus a decrease of corrosion resistance. Pyrogallic treated nitinol surfaces (with a corrosion rate of 0.119 mm/year) are half as electrochemically corrosion resistive as tannic acid‐coated substrate. Therefore, it is proposed that tannic treated nitinol would be a better option if implanted on biomaterial surfaces.